Prevalence of intestinal parasite contamination in raw vegetables and school soil samples in Koh Yao, Phang Nga Province, southern Thailand. - Udomsak Narkkul; Prasit Na-Ek; Aulia Rahmi Pawestri; Chuchard Punsawad (PLoS ONE)
Parasitic infections remain a significant public health issue in Thailand. Exposure to intestinal parasites occurs through consumption of improperly washed raw vegetables and handling of contaminated soil without proper hygiene. This study assessed the prevalence of intestinal parasites in raw vegetables and school soil, along with the associated factors, in Koh Yao, Phang Nga Province, Thailand. Vegetables (21 types) were collected from local markets and stores in Koh Yao Noi, Koh Yao Yai, and Phru Nai. Moreover, soil samples were collected from playgrounds, football fields, sidewalks, schoolyards, and areas around cafeterias in 13 public primary schools. Approximately 2.3% of vegetable samples (3 out of 131) were contaminated with parasites (one peppermint and two Chinese morning glory samples). The most commonly detected parasites were Ascaris spp. eggs (1.5%) and hookworms (0.8%). Koh Yao Noi had the highest contamination rate of 7.1%, whereas no contamination was observed in samples from Koh Yao Yai and Phru Nai. The contamination rates in vegetables obtained from the three subdistricts showed significant differences (p <  0.05). All contaminated vegetables were grown locally. In soil samples, parasites were detected in 11 of the 13 schools (84.6%). Of the 141 soil samples, 42 (29.8%) were contaminated, and Toxocara spp. were found in all contaminated samples. Phru Nai had the highest soil contamination rate (50%), followed by Koh Yao Yai (20.5%), and Koh Yao Noi (11.4%). There were significant differences in the distribution of parasite contamination across the three subdistricts (p <  0.001) and seasons (p <  0.001). Football fields were the most contaminated areas, with 36% of samples testing positive for parasites. This study highlights the risk of parasitic transmission through contaminated vegetables and soil. Hence, this emphasizes the need for health authorities to educate local communities on proper hygiene practices, including hand washing and thorough vegetable cleaning, to prevent parasitic infections. Implementing preventive measures in schools and communities is crucial for limiting parasitic disease spread.